'Are you being your best?' Why students behave responsibly. (November 2015) - Fogelgarn, Rochelle Karen; Lewis, Ramon (Rom)
Undiscerning obedience to authority or compliance motivated by social approval differs substantially from volitional moral reasoning based on internalized values. The aim of this study was to ascertain why students would choose to act responsibly in the absence of external constraints. This article reports data collected from primary students in 10 Australian schools, who described the reasons why they would choose to act responsibly. Data analyses identified eight motives which, when categorized, appeared to derive from obedience, compliance or volition. The discussion of results suggests a socially significant difference between students acting responsibly and being responsible. We contend that morally driven classroom management practices are likely to produce more self-aware, morally autonomous, responsible students who conscientiously aspire to be the best that they can be at all times.